Women’s Refugee Commission in Integrating Gender Perspectives into Humanitarian Aid to Respond to the Myanmar Refugee Crisis - Walda Okvi Juliana Ningsih (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. This study focuses on examining how the Women's Refugee Commission (WRC) integrates a gender lens into humanitarian aid practices for Myanmar refugees. Conflict or war has different influences and impacts on men and women, so it is important to use a gender lens when conducting humanitarian actions. Gender makes women and men vulnerable to the effects of conflict or war, but in different ways. Refugee women, girls, and children as vulnerable groups face multiple risks, ranging from limited access to basic services, economic, health, environmental, personal, and political aspects, trauma, and even gender-based violence, both direct violence and structural violence. Using a qualitative case study approach, this research explores the strategies, challenges, and contributions of WRC in ensuring that humanitarian aid is more inclusive and responsive to the specific needs of women and children. The results of this study show that gender mainstreaming by WRC increases the effectiveness of humanitarian responses and strengthens the resilience of refugee communities. This study concludes that gender matters in humanitarian action or assistance because it provides a more accurate understanding of the situation by recognizing the differences between women and men, girls and boys, and ensuring that humanitarian assistance programs fully integrate the principle of non-discrimination. Keywords: Humanitarian Aid, Gender, Refugees, Women’s Refugee Commission, Myanmar Crisis. Abstrak. Penelitian ini fokus mengkaji bagaimana peran Women’s Refugee Commission (WRC) mengintegrasikan lensa gender ke dalam praktik humanitarian aid bagi pengungsi Myanmar. Konflik atau perang memiliki pengaruh dan dampak yang berbeda terhadap laki-laki dan perempuan, sehingga penting untuk menggunakan lensa gender ketika melakukan aksi kemanusiaan. Gender membuat perempuan dan laki-laki rentan terkena dampak konflik atau perang namun dalam hal yang berbeda. Pengungsi perempuan, gadis dan anak-anak sebagai kelompok rentan menghadapi risiko berlapis, mulai dari keterbatasan akses pada layanan dasar, segi ekonomi, kesehatan, lingkungan, personal, politik, rasa trauma, bahkan menerima kekerasan berbasis gender baik kekerasan secara langsung (direct violence) maupun kekerasan sturuktural (structural violence). Dengan pendekatan kualitatif studi kasus, penelitian ini mengeksplorasi strategi, tantangan, dan kontribusi WRC dalam memastikan bahwa bantuan kemanusiaan lebih inklusif dan responsif terhadap kebutuhan spesifik perempuan dan anak. Hasil penelitian ini menunjukkan bahwa pengarusutamaan gender oleh WRC meningkatkan efektivitas respons kemanusiaan dan memperkuat resiliensi komunitas pengungsi Penelitian ini menyimpulkan bahwa dalam melakukan tindakan atau bantuan kemanusiaan, gender itu penting (gender matters) karena memberikan pemahaman yang lebih akurat tentang situasi, dengan mengenali perbedaan antara perempuan dan laki-laki, anak perempuan dan anak laki-laki dengan memastikan program bantuan kemanusiaan mengintegrasikan sepenuhnya prinsip non-diskriminasi. Kata Kunci: Bantuan Kemanusiaan, Gender, Pengungsi, Women’s Refugee Commission, Krisis Myanmar.